Seating position, seat belt wearing, and the consequences in facial fractures in car occupants (Clinics, 2007)
INTRODUCTION: Trauma caused by traffic accidents is among the main etiologies involved in the occurrence of facial fractures throughout the world. However, the trauma mechanisms involved are different according to the location where the study was performed, due to different conditions of development, legislation, and culture. A retrospective study was done between February 2001 and July 2006, with the purpose of determining the epidemiology and the mechanisms involved in the occurrence of facial fractures among car occupants in the metropolitan area of São Paulo. METHODS: Data were collected from 297 patients admitted with facial fractures to the emergency room of the Hospital das Clínicas, São Paulo University Medical School. Within this period, 151 individuals had been involved in traffic accidents, among which 56 (37.08%) were inside passenger cars. These were grouped based on the seating position that they were occupying at the time of the accident and the wearing of seat belts. Data concerning the number and location of fracture lines were obtained from the different groups, and a fracture/patient index (F/P I) was calculated to compare and make reference to the impact energy among these groups, for subsequent analysis and discussion. RESULTS: 323 fracture lines occurred among 56 patients who were car occupants. By applying the F/P I, we obtained higher values in the group of rear-seat passengers who were not wearing seat belts (7.23 fractures per patient), followed by the group of drivers not wearing seat belts (6.33 fractures per patient), the group of front-seat passengers not wearing seat belts (5.58 fractures per patient), the group of drivers wearing seat belts (5.54 fractures per patient) and, finally, the group of front-seat passengers wearing seat belts (4.00 fractures per patient). None of the rear-seat passengers was wearing seat belts. CONCLUSION: The data collected indicate that the driver position shows a high incidence of facial fractures, not being effectively protected by the seat belt, although the wearing of seat belts seems to have a protective role against the occurrence of facial fractures in front-seat passengers. It was not possible to evaluate the wearing of seat belts among rear-seat passengers, even though the high incidence of fractures in this group showed its high susceptibility to the occurrence of facial fractures, which highlights the need of taking protective measures against this situation.